Penyakit Prioritas di Kabupaten Badung: - - Made Agus Sugianto (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2021)
Background: The Central Government and Local Governments including Badung Regency are facing the burden of communicable and non-communicable diseases which has not ended until now. Purpose: to find out the most priority diseases to be prevented and controlled in Badung Regency. Methods: This is a descriptive-analytic study using secondary data from monthly reports of outpatient visits and inpatients at the health center and the Mangusada Regional Hospital during 2014 - 2018. Besides, interviews were also conducted with respondents with a health education background. Results: The scoring results show Hypertension as the first ranked disease to be treated in Badung Regency with a score of 63.8. This disease is classified as a non-communicable disease group. The disease that is ranked second is HIV / AIDS which is an infectious disease with a score of 58.9, and the third rank is occupied by Diabetes Mellitus, which is also a non-communicable disease with a score of 58.7. Conclusion: Based on the results of the interview, hypertension is the most priority disease to be tackled in Badung Regency in 2019. The second and third priority diseases are respectively occupied by HIV / AIDS and Diabetes Mellitus. Latar belakang: Pemerintah Pusat maupun Pemerintah Daerah termasuk Kabupaten Badung menghadapi beban penyakit menular dan penyakit tidak menular yang tidak kunjung usai sampai dengan saat ini. Tujuan: untuk mengetahui penyakit yang paling prioritas untuk dicegah dan dikendalikan di Kabupaten Badung. Metode: adalah penelitian deskriptif analitik menggunakan data sekunder laporan bulanan kunjungan pasien jalan dan pasien rawat inap di puskesmas serta RS Daerah Mangusada sepanjang tahun 2014 – 2018. Selain itu, juga dilakukan wawancara kepada responden dengan latar belakang pendidikan kesehatan. Hasil: Hasil scoring menunjukan Hipertensi sebagai penyakit ranking pertama untuk ditangani di Kabupaten Badung dengan nilai score 63,8. Penyakit ini tergolong dalam kelompok penyakit tidak menular. Penyakit yang menduduki ranking kedua adalah HIV/AIDS yang merupakan penyakit menular dengan nilai score 58,9, dan ranking ketiga diduduki oleh penyakit Diabetes Melitus yang juga penyakit tidak menular dengan nilai score 58,7. Simpulan: Hipertensi merupakan penyakit yang paling prioritas untuk ditanggulangi di Kabupaten Badung pada tahun 2019. Penyakit kedua dan ketiga yang menjadi prioritas masing-masing ditempati oleh penyakit HIV/AIDS dan Diabetes Melitus.